Metodologia de gamificação para ações de marketing social na doação voluntária de sangue - Serrano, Paulo Henrique Souto Maior (2019)
This thesis establishes practical guidelines for a social marketing approach with game elements. It is specifically a gamification methodology for social marketing actions in the context of voluntary blood donation. The paper also implements and evaluates the proposed methodology in Paraíba’s blood center through a progressive web application (PWA) named Pontos de Vida. Voluntary blood donation conditions the treatment of several clinical patients, as well as accident victims. In Brazil, voluntary action is constantly subject to social marketing campaigns that aim to increase the stocks of blood centers. The context of this thesis fits into the scope of social marketing for having as a goal the behavioral change for the improvement of individual and societal well-being. The paper is also based on transformative consumer research (TCR), endorsing that the promotion of a practice is what potentially changes the current circumstances and improves social well-being. The methodology used in the development of the thesis is based on the Design Science Research (DSR) paradigm, which is based on the search for relevance of studies and the approximation between theory and practice in a way that it is applicable to real situations. The research work carried out here has sought to develop practical guidelines for the execution of a gamified methodology, relating it to the demands of social marketing actions. The proposed gamified methodology was distributed in steps which consisted of: 1) Pre-existing knowledge activation; 2) Place of practice recognition; 3) Players characterization; 4) Variables identification; 5) Game elements implementation; 6) Game testing and evaluation of indicators. These steps were implemented in the development of a smartphone-based technological solution called Pontos de Vida. The progressive web app was implemented in the blood center as a way to demonstrate the application of the methodology. The approach with game elements proposed here has been proved to be relevant in its potential to reach a larger public interest for voluntary blood donation. In three weeks, 184 users were accounted for, 213 informative contents were viewed, 52 intentions to return to the blood center within 3 months were registered and 17 actual donations were recorded. The gamified approach brought by this thesis has represented an incentive for voluntary blood donation. The use of game elements can be utilized by professionals and practitioners to implement social marketing strategies in different contexts, bringing benefits to the population in a ludic way.